Autoformação do ser gestor Marista preconizada à luz do projeto educativo do Brasil Marista - Mentges, Manuir José (2013)
The present paper researched about the self-training Being Maristas Manager, inspired in Educative Project, document that gives singleness to Maristas Brazil educatives process, in respect to diversities. It depicts some aspects of my personal career, related to work with education and management, research weaved its process starting problem-question: How do the perspectives and horizons related self-training being Maristas manager aimed to Maristas Brazil s Educational Project, it makes present in everyday exercise s management? From, that the paper objected understanding the management s process, advocated the light of education project, it is deepening your horizons and your implications in self-training of Being Maristas Manager. The research sought to go your, with goals through study, with qualitative approach, descriptive and interpretative, that, to Bogdan and Biklen (1994), it concerns with process, by being inductive and having as essential significance. The research developed at Graças Maristas Institute, located on Viamão city, school in which I assumed the role of Director in 2012. The subjects of the research were team members managers directive, that include the Director, the Vice-Director, the Pedagogical Co-ordination, Shift s Co-ordination, the Educational Guidance and Pastoral s Co-ordination. The paper was developed in stages structured blocks, with objectives and guiding questions.The Educative Project and others Maristas documents, that have devoted authors especially in Management and Spirituality s areas, referential. The research revealed constitutive elements, to self-training Being Maristas Manager, and a clear perception of reality of our school, it is approaching the current reality of the ideal aimed at educational project. It perceived the full importance of training managers, in all dimensions, as well as the importance of spirituality, as a cross element that gives flavor and life to mission. Promoting a great personal growth, this paper also fermented the revision and improvement systemic processes of administrative-pedagogical-pastorals, pointing the possibility of internal and external actions of the management team, the cultivation of an organizational climate and, people s appreciation, culminating with a evangelizing education quality.